Análise técnico-econômica de um sistema de geração eólica para uma unidade armazenadora e secadora de grãos - Basso, Thalyta Mayara (2017)
One of the biggest concerns in the contemporary world is the overuse of electricity. Along with that, in the last few years, the growth of investment in the sector of wind and solar power generation has stood out, which has contributed to supply for the needs faced by Brazil due to unfavorable hydrological conditions, which impair the production in the water power plants. Thus, a study was done on the technical and economic feasibility of the implantation of a small wind powerhouse in a grain warehouse, located in São João do Oeste, district of Cascavel-PR, to supply the power needs of such a building. Based on data provided by SIMEPAR, for every 10 meters of height, the annual/daily average of wind speed in the area was 4,12 m/s, the average temperature was 20,4 ºC and the average air pressure was 937,81 hPa, considering the last 5 years of measuring. Through the technical analysis and the cost survey, the decision was taken to use 3 turbines of 80 kW of power, at 30 meters of height, which would supply about 80% of the power needs in the place, generating credit in the months of low consume to be used in the months of higher use. However, the budget also proved to be unfeasible by the Net Present Value Method, the Internal Rate of Return and the Deducted Pay-Back as well, determining that at the end of the useful life of the turbines, the investment wouldn’t have been paid and it would be necessary to change the equipment, creating a debt over debt for the investor. Comparing the cost of such an investment in Brazil to other countries, a variation of 529% was observed, and the Brazilian cost for the system adopted is R$25.625,00/kW, while the foreign average is R$4.843,34/kW; Such a difference could be related to importation rate, taxes, reduced popularization and the competition between suppliers in Brazil